2014
DOI: 10.5194/amt-7-2147-2014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of GOMOS ozone precision estimates in the stratosphere

Abstract: Abstract. Accurate information about uncertainties is required in nearly all data analyses, e.g., inter-comparisons, data assimilation, combined use. Validation of precision estimates (viz., the random component of estimated uncertainty) is important for remote sensing measurements, which provide the information about atmospheric parameters by solving an inverse problem. For the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument, this is a real challenge, due to the dependence of the signal-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…The estimated random uncertainty of GOMOS ozone profiles in the stratosphere is 0.5-5 % . Validation of estimated uncertainties for ozone profiles in the stratosphere has shown that they are realistic except for cases when ozone profiles are derived from occultations of dim stars (Sofieva et al, 2014b).…”
Section: Gomosmentioning
confidence: 99%
“…The estimated random uncertainty of GOMOS ozone profiles in the stratosphere is 0.5-5 % . Validation of estimated uncertainties for ozone profiles in the stratosphere has shown that they are realistic except for cases when ozone profiles are derived from occultations of dim stars (Sofieva et al, 2014b).…”
Section: Gomosmentioning
confidence: 99%
“…The estimated random uncertainty of GOMOS ozone profiles is 0.5-5 % in the stratosphere and 1-10 % in the mesosphere and lower thermosphere. Validation of the uncertainty estimates for ozone profiles in the stratosphere has shown that they are realistic except for dim stars (Sofieva et al, 2014a).…”
mentioning
confidence: 99%
“…The parameter S diff / √ 2 is a direct analogue of the integral of the structure function from the theory of random functions. More details can be found in Sofieva et al (2014) and Laeng et al (2015). In Fig.…”
Section: Precision Validationmentioning
confidence: 99%
“…While the direct comparison is often affected by natural variability within the collocation radius, the approach chosen here aims at solving this problem by statistically comparing the differences as a function of spatiotemporal distance. This approach was used in Sofieva et al (2014) and Laeng et al (2015) for the evaluation of the quality of uncertainty estimates provided by GOMOS (Global Ozone Monitoring by Occultation of Stars) and MIPAS ozone measurements.…”
Section: Precision Validationmentioning
confidence: 99%